EVALUASI DAN IMPLEMENTASI SISTEM SURVEILANS DEMAM BERDARAH DENGUE (DBD) DI KOTA SINGKAWANG, KALIMANTAN BARAT, 2010 - Frans yosep sitepu; Antonius Suprayogi; Dibyo Pramono (Balai Penelitian dan Pengembangan Kesehatan Banjarnegara Badan Litbangkes Kemenkes RI, 2012)
Introduction: Dengue Haemorrhagic Fever (DHF) is still a public health problem in Singkawang Municipality which was an endemic area. DHF surveillance is expected to inform endemicity of an area, season of transmission and disease progression that can be use to make the system more effective and efficient. Methods: Observational study by using a structured questionnaire. Interview was conducted to all DHF surveillance officers. Evaluated had been done to the variable of input, process, and output of the surveillance system. We conducted an on the job training to all DHF surveillance officers after the evaluation.Results: 66.7% officers never got any trainings of surveillance, 83.3% had double duty, budgeting limited to physical needs, facilities and infrastructures. Process variable, data collection was late; analysis and recommendation had not been directed to the distribution of cases, the relationship between risk factors and the mortality of DHF incidence, and environment changing, feedback; data distribution had not been implemented optimally. Output variable was still weak, no surveillance epidemiology profile. Attribute surveillance such as simplicity, flexibility, and positive predictive value were good, but still weak in acceptability, sensitivity, representativeness, and timeliness. Short-term evaluation resulted that there was an increasing knowledge of surveillance officers (p value <0.05). Mid-term evaluation resulted that there was an increasing of completeness and accuracy of DHF report from 80% to 100%, active case finding, epidemiology investigation conducted to all DHF cases.Discussion and Conclusions : DHF surveillance system in Singkawang needs to be improved, there were many attributes of surveillance system that had not done well. Training of surveillance system is needed to improve capability and capacity of the surveillance officers.